Catalyst Genesis : A Virtual Reality Application On Cryptocurrency Revolution - Mohamad Farid Zamri; Azir Rezha Norizan (Journal of Computing Technologies and Creative Content, 2022)
Virtual reality (VR) is a computer-generated simulation that allows you to operate electronic devices such as glasses with screens and gloves with sensors in an artificial three-dimensional environment. Malaysian citizens are not yet fully aware of cryptocurrencies and their benefits, despite the fact that technology has existed for quite some time. Lack of knowledge and sources of cryptocurrency among Malaysians, and their doubts about their credibility. This research aims to develop an interactive virtual reality walkthrough application for cryptocurrencies that uses both Blender and Unity. It focuses on the capabilities of cryptocurrencies, how they work, and their availability or readability in Malaysia. Therefore, this study aims to analyze the level of acceptance and knowledge of cryptocurrencies such as Bitcoin among Malaysians in order to develop virtual reality applications that teach Malaysian citizens how cryptocurrencies work. increase. In my current research, I used agile techniques to create practical resources to support VR application development. The target group for this project is men and women aged 18-35 years. The implementation of this project is planned by sending it to the Windows Store or an exe file for publication and distribution. In short, this study will help improve the understanding of cryptocurrencies through virtual reality walkthrough.